The role of exploration and exploitation in design for luxury fashion brands - Pedro, Yael (2019)
This thesis investigates how exploration and exploitation are expressed through designer activities in design for luxury brands. Exploration and exploitation are more visible in luxury brands than in non-luxury brands. Some of their dimensions are explicit and display exploration and exploitation attributes. The research aims to study designer activities through a managerial lens, a perspective that can magnify how exploration and exploitation are expressed in the design process. The brand’s strategic planning could benefit from understanding how knowledge evolves through the design process and translates into a product. This study follows an exploratory approach based on multiple interviews with luxury fashion and product designers from around the world. The findings propose some insights into the different roles of exploration and exploitation that are expressed through the design process.